The Multiple Waves of the African Academic Diaspora’s Engagement with African Universities - O Oanda, Ibrahim; Obonyo, Mark M (International Journal of African Higher Education, 2021)
This article analyses the various historical phases in the evolution of the African academic diaspora’s engagement to support the development of higher education in Africa. It examines the drivers and motivation for such engagement and its implications for higher education development on the continent. The data were derived from a critical review of secondary sources, supplemented by primary observations by one of the authors who is engaged in a programme that supports diaspora academics to travel to African universities for engagement, as part of the third wave. The analysis of the secondary material shows that while the first wave of engagement was driven by a strong sense of Pan-Africanism at the global level and laid the foundation for the establishment of universities across the continent, the second wave became trapped in Cold War rivalries that limited engagement and drove more academics from African universities into exile, mainly in Europe and North America, thus swelling the ranks of diaspora academics. The third wave has been caught up in a similar situation. While the forces of globalisation and internationalisation that are driving this wave of diaspora engagement have the potential to support African universities to achieve international standards, they can equally undermine and mute the desire for higher education decolonisation. The article recommends that African countries and higher education institutions should play a central role in designing the broad policy context that drives engagement and that the activities undertaken by African diaspora academics should align with national higher education priorities.